EFFECT OF SEASON ON LENGTH-TENSION RELATION OF GASTROCNEMIUS MUSCLE OF UROMASTIX HARDWICKII - MA, Azeem; HA, Shaikh (Pakistan Journal of Physiology, 2006)
Background: Seasonal variations in the biological activities of animals are commonly reported in literature. However, these variations are not studied yet in correlation with the structure and function of skeletal muscles in general and their mechanics in particular. Methods: This study was conducted on skeletal muscles of a reptile, Uromastix, to determine the effect of season on the shape of length-tension curves, active tension, passive tension and tension equilibrium length (TEL). Results: Result demonstrates that active tension obtained from gastrocnemius muscle was found to increase significantly from the winter (December) to peak summer month (June), which showed a significant fall till the second winter (December). The passive tension was also found to increase significantly (P<0.0005) from winter (December) to peak summer (June) which also decreased significantly till the second winter (December). Change in both the active and passive tensions has resulted in a rise in the average values of tension equilibrium length from the winter (December) to peak summer (June) and fall till second winter (December). Conclusion: It is concluded that length-tension parameters exhibit variations between different seasons and reflects a dominancy of contractile elements towards summer and elastic elements towards winter in the gastrocnemius muscles of Uromastix.